High-Temperature First-Order-Reversal-Curve (FORC) Study of Magnetic Nanoparticle Based Nanocomposite Materials. (4th September 2017) - Dodrill, B.; Ohodnicki, P.; McHenry, M.; Leary, A.
Abstract: First-order-reversal-curves (FORCs) are an elegant, nondestructive tool for characterizing the magnetic properties of materials comprising fine (micron- or nano-scale) magnetic particles. FORC measurements and analysis have long been the standard protocol used by geophysicists and earth and planetary scientists investigating the magnetic properties of rocks, soils, and sediments. FORC can distinguish between single-domain, multi-domain, and pseudo single-domain behavior, and it can distinguish between different magnetic mineral species [1]. More recently, FORC has been applied to a wider array of magnetic material systems because it yields information regarding magnetic interactions and coercivity distributions that cannot be obtained from major hysteresis loop measurements alone. In this paper, we will discuss this technique and present high-temperature FORC results for two magnetic nanoparticle materials: CoFe nanoparticles dispersed in a SiO2 matrix, and FeCo-based nanocrystalline amorphous/nanocomposites.